Are disruptive innovations recognised in the healthcare literature? A systematic review. Issue 1 (4th September 2020) - Sounderajah, Viknesh; Patel, Vanash; Varatharajan, Lavanya; Harling, Leanne; Normahani, Pasha; Symons, Joshua; Barlow, James; Darzi, Ara; Ashrafian, Hutan
Abstract : The study aims to conduct a systematic review to characterise the spread and use of the concept of 'disruptive innovation' within the healthcare sector. We aim to categorise references to the concept over time, across geographical regions and across prespecified healthcare domains. From this, we further aim to critique and challenge the sector-specific use of the concept. PubMed, Medline, Embase, Global Health, PsycINFO, Maternity and Infant Care, and Health Management Information Consortium were searched from inception to August 2019 for references pertaining to disruptive innovations within the healthcare industry. The heterogeneity of the articles precluded a meta-analysis, and neither quality scoring of articles nor risk of bias analyses were required. 245 articles that detailed perceived disruptive innovations within the health sector were identified. The disruptive innovations were categorised into seven domains: basic science (19.2%), device (12.2%), diagnostics (4.9%), digital health (21.6%), education (5.3%), processes (17.6%) and technique (19.2%). The term has been used with increasing frequency annually and is predominantly cited in North American (78.4%) and European (15.2%) articles. The five most cited disruptive innovations in healthcare are 'omics' technologies, mobile health applications, telemedicine, health informatics and retail clinics. The concept 'disruptive innovation' has diffused into the healthcare industry. However, its use remains inconsistent and the recognition of disruption is obscured by other types of innovation. The current definition does not accommodate for prospective scouting of disruptive innovations, a likely hindrance to policy makers. Redefining disruptive innovation within the healthcare sector is therefore crucial for prospectively identifying cost-effective innovations.